Organ Systems Dependent on Nitric Oxide and the Potential for Nitric Oxide‐Targeted Therapies in Related Diseases - Hollenberg, Norman K. (J Clin Hypertens (Greenwich), 2007)
Nitric oxide (NO) is a universal messenger molecule that plays diverse and essential physiologic roles in multiple organ systems, including the vasculature, bone, muscle, heart, kidney, liver, and central nervous system. NO is produced by 3 known isoforms—endothelial, neuronal, and inducible NO synthase—each of which perform distinct functions. Impairment of NO bioactivity may be an important factor in the pathogenesis of a wide range of conditions, including preeclampsia, osteoporosis, nephropathy, liver disease, and neurodegenerative diseases. Although increased levels of NO synthase or NO bioactivity have been associated with some of these disease states, research increasingly suggests that preservation or promotion of normal NO bioactivity may be beneficial in reducing the risks and perhaps reversing the underlying pathophysiology. Based on this rationale, studies investigating the use of NO‐donating or NO‐promoting agents in some of these diseases have produced positive results, at least to some degree, in either animal or human studies. Further investigation of NO‐targeted therapies in these diverse diseases is clearly mandated.